Reactivation, Oxidation And Surface Functionalization Of Spent Activated Carbon For Glycerin Decolourization - Choo, Hong Han (Universiti Sains Malaysia, 2018)
After continuous use in adsorption process, the spent AC will be saturated and unable to remove targeted adsorbate effectively. In this research, spent activated carbon was reconverted into useful adsorbent via a re-activation process, followed by oxidation and functionalization process to the carbon materials. Oxidation of the surface of reactivated carbon was carried out to further improve the adsorption capacity of the reactivated carbon. Oxidation of activated carbon was done with using chemical oxidation of HNO3. Functionalization of the reactivated and oxidized carbon was introduced through hydrophobic treatment, for better glycerin decolourization. Ethylamine (EA) was used in the hydrophobic treatment. FTIR was done toward all carbon material to conclude the presence of functional group of COO- and CN bond. The adsorption of glycerin product was evaluated before and after the hydrophobic functionalization. Functionalization improved carbon adsorption of glycerin product by around 2.1%. Besides, performance comparison of was decolourization was conducted between industrial sample and lab sample was done. Lab RAC shows better result then industry sample by 4.6%.